2022
DOI: 10.1002/suco.202100763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid‐activation on CaO existential state and reactive properties of hot‐splashed steel slag in cement‐based materials

Abstract: The over-burnt free-CaO(f-CaO) existential state in hot-splashed steel slag is understood by observing the microstructure of steel slag section and analyzing the minerals in the steel slag (SS). In the investigation, a new method of using hydrochloric acid as the solvent to modify the steel slag powder (SSP) is put forward. The effects of hydrochloric acid pretreatment on the surface morphology of SS and the hydration activity and soundness of SSP blended cement are investigated. Furthermore, the failure mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…(2) To improve the strength of the concrete, it is necessary to reduce and refine the pore sizes 38 . The hydration reaction of f‐CaO in SSA is slow, and the volume of calcium hydroxide (CH) produced by the hydration reaction of f‐CaO is 98% higher than that of f‐CaO 12,39 . The SEM result depicted in Figures 12c and 13c showed that the formation of the CH in the SSC mixture compared to the normal concrete.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) To improve the strength of the concrete, it is necessary to reduce and refine the pore sizes 38 . The hydration reaction of f‐CaO in SSA is slow, and the volume of calcium hydroxide (CH) produced by the hydration reaction of f‐CaO is 98% higher than that of f‐CaO 12,39 . The SEM result depicted in Figures 12c and 13c showed that the formation of the CH in the SSC mixture compared to the normal concrete.…”
Section: Resultsmentioning
confidence: 99%
“…38 The hydration reaction of f-CaO in SSA is slow, and the volume of calcium hydroxide (CH) produced by the hydration reaction of f-CaO is 98% higher than that of f-CaO. 12,39 The SEM result depicted in Figures 12c and 13c showed that the formation of the CH in the SSC mixture compared to the normal concrete. The low content of f-CaO in the SSA can fill the microcracks and ITZ in the later hydration reaction.…”
Section: Enhancement Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, the global emissions of steel slag have exceeded 1.5 billion tons. More than 500 million tons of untreated steel slag have been accumulated, leading to occupation of lands and potential pollution of water and soil because of the alkaline leachates from steel slag 1–4 …”
Section: Introductionmentioning
confidence: 99%
“…More than 500 million tons of untreated steel slag have been accumulated, leading to occupation of lands and potential pollution of water and soil because of the alkaline leachates from steel slag. [1][2][3][4] On the other hand, the consumption of concrete in engineering construction is huge, but the natural aggregate is increasingly exhausted, which makes the search for the Discussion on this paper must be submitted within two months of the print publication. The discussion will then be published in print, along with the authors' closure, if any, approximately nine months after the print publication.…”
Section: Introductionmentioning
confidence: 99%